NUCLEAR MEDICINE AS A CONTEMPORARY STUDY SUBJECT - Pocherniaeva, V.F.; Vasko, L.N.; Zhukova, T.A. (World of Medicine and Biology, 2017)
The problem of medical education at the present stage of development is considered. An effective solution to the health problem consists in the adequate formulation and solution of the issue of training high-level personnel in nuclear medicine competence. the main importance of the level of professionalism of radiology doctors is acquired during the diagnosis and treatment of cancer patients.